Indikator Kinerja dan Reformasi Birokrasi : Tinjauan Terhadap Indikator Kinerja Dalam Instrumen Pengukuran Kinerja Organisasi Pemerintah - tin, Suwa (Pusjar SKPP Lembaga Administrasi Negara, 2010)
Bureaucracy Reform is a national program consists of three pillars; organization structure and design, business processes, and human resources. Since government is a huge complex system with hierarchy, formal and rigid rules, therefore to succeed the reform, it must be executed gradually but systematically, consistently, and seriously (Effendi, 2009). With this conception, organizational performance evaluation for government organization becomes an essential tool supporting the continuity and the consistency of reforms as evaluation provides judgement and information of where we are now - the present performance, and hence would assist to find what next steps to run for achieving the better performance suitable to the final goal. Expectation of evaluation benefits implies the requirement of reliable peformance indicators that suitable to the soul and the goal of the reform in which transparency and accountability are among them. Based on this opinion, this paper discusses the expectation of bureaucratic reform, the peformance indicators of available instrument of performance evaluation, the concepts of performance evaluation, and some alternatives that could be adopted to improve the prevailing performance indicators. Keywords : Reformasi Birokrasi, Indikator Kinerja Organisasi Pemerintah, Efisiensi, Akuntabilitas, dan Pengembangan Instrument Pengukuran Organisasi.